Challenges on implementation of art and design curriculum in secondary schools in Kenya - Ongachi, Wagah Mical; Okwara, Michael O.; James, Awino (Academic Research International, 2013)
Art and Design Curriculum contributes immensely in all areas of the society such as Social/cultural, Economic, Political, Utilitarian, Communication and Personal expression. This subject interlocks strongly within the political, economic and social cultural fabric of the Nation. In spite of the important role played by Art and Design Curriculum its implementation in secondary schools has not been impressive owing to some schools dropping this curriculum in Western Kenya. This implies that the Art and Design Curriculum has not been effectively implemented. The purpose of the study was, therefore, to examine implementation of secondary school Art and Design Curriculum. The study used descriptive survey. The research was carried out in Western Kenya. The main objective of the study was to identify the challenges to implementation of Art and Design Curriculum. Data was collected from Head teachers, teachers and students using Questionnaire and Observation guide. Many schools had only one Art and Design Curriculum teacher. The study also revealed that many teachers of Art and Design Curriculum had a bachelor of education degree but some teachers were untrained. Art room observation revealed inadequacy of facilities for Art and Design implementation. It is recommended that the Ministry of education should step up both the facility fund allocated for this subject and the number of teachers employed to teach Art and Design Curriculum.
Keywords: Challenges; Curriculum; Art and Design